2021
DOI: 10.1093/bjsw/bcab163
|View full text |Cite
|
Sign up to set email alerts
|

Australian and New Zealand social workers adjusting to the COVID-19 pandemic

Abstract: In 2020, social workers across the world responded to the global COVID-19 pandemic and the consequent strict lockdown procedures over several months. In many countries, including Australia and New Zealand, this virtual shutdown period necessitated a reframing of social work practice to incorporate factors including delivery of services via virtual means and more limited access for vulnerable clients. This article draws on the integration of two methods designed to address the research question: ‘How has social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
(63 reference statements)
1
13
0
Order By: Relevance
“…The workload of social care organisations has increased their users' needs grow, related to health issues, isolation, financial concerns, domestic violence and homelessness (Alston et al, 2021;Nisanci et al, 2020). Alston et al (2021) have also focussed on the lack of media coverage concerning the essential work carried out by social workers during the pandemic. Despite the previously mentioned disadvantages, some studies have also reported positive aspects of teleworking in social care, such as reduced travel time, digitalisation and working from home as a "more effective and peaceful" experience (Forsberg, 2021), in addition to opportunities for digital j INTERNATIONAL JOURNAL OF MIGRATION, HEALTH AND SOCIAL CARE j health care and for providing information, guidance and protection (Thomas et al, 2021).…”
Section: Health Organisation and Communication Crisismentioning
confidence: 99%
See 4 more Smart Citations
“…The workload of social care organisations has increased their users' needs grow, related to health issues, isolation, financial concerns, domestic violence and homelessness (Alston et al, 2021;Nisanci et al, 2020). Alston et al (2021) have also focussed on the lack of media coverage concerning the essential work carried out by social workers during the pandemic. Despite the previously mentioned disadvantages, some studies have also reported positive aspects of teleworking in social care, such as reduced travel time, digitalisation and working from home as a "more effective and peaceful" experience (Forsberg, 2021), in addition to opportunities for digital j INTERNATIONAL JOURNAL OF MIGRATION, HEALTH AND SOCIAL CARE j health care and for providing information, guidance and protection (Thomas et al, 2021).…”
Section: Health Organisation and Communication Crisismentioning
confidence: 99%
“…Infodemic vs scarce migration information Alston et al (2021) have analysed the lack of media coverage in Australia and New Zealand concerning the essential work of social workers during the pandemic. In our current study, the vast majority of respondents believe that media coverage about migration has been scarce and even biased as follows:…”
Section: Infodemic: An Additional Communicative Effortmentioning
confidence: 99%
See 3 more Smart Citations